Measured energy expenditure in mildly hypothermic critically ill patients with traumatic brain injury: A sub-study of a randomized controlled trial. Issue 6 (June 2021) - Ridley, Emma J.; Davies, Andrew R.; Bernard, Stephen; McArthur, Colin; Murray, Lynne; Paul, Eldho; Trapani, Antony; Cooper, D James
Summary: Background & aims: Prophylactic hypothermia, often used in critically ill patients with traumatic brain injury, reduces energy expenditure and may affect energy delivered by nutrition therapy. The primary objective of this study was to measure energy expenditure in hypothermic patients over the first 3 days after traumatic brain injury (TBI). Secondary objectives included comparison of measured energy expenditure and nutrition delivery to day 7. Methods: A prospective sub-study of a randomized controlled trial conducted in patients with severe TBI, investigating prophylactic hypothermia (33–35 °C) as a neuroprotective therapy. In two centers, indirect calorimetry was initiated within 24 h of randomization and repeated up to twice daily to day 7. Data are presented as n (%), mean (standard deviation (SD)), median [interquartile range (IQR)], and mean difference (95% confidence interval (CI)). Results: Forty patients were included (20 in each group), with 17 patients in the hypothermic and 16 in the normothermic group having an indirect calorimetry measurement in the first 3 days. Over the first 3 days, the mean temperature in the hypothermic and normothermic groups was 33.5 (0.6) ºC (n = 17) and 37 (0.5) ºC (n = 16), p < 0.0001, and the mean measured energy expenditure, was 21 (5) and 27 (4) kcal/kg, p = 0.002, representing a mean difference of 5 (95% CI: 2–8) kcal/kg. Energy expenditure was 20% (95% CI: 9.5–29%) less in hypothermia patients compared to normothermia patients. Hypothermia patients also had higher gastric residual volumes across the 7 day study period (438 (237) mls vs 184 (103) mls, p < 0.0001) and higher use of metoclopramide and erythromycin as prokinetics. Despite enteral nutrition intolerance, hypothermia patients received 93% of measured energy expenditure over 7 days. Conclusion: In TBI patients, energy expenditure was 20% less when receiving prophylactic hypothermia compared to normothermia. Greater gastric residual volumes, use of prokinetics and energy delivery that approximated measured energy expenditure was also observed in hypothermia patients. Trial registry number: POLAR-RCT: clinicaltrials.gov Identifier: NCT00987688; Anzctr.org.au Identifier: ACTRN12609000764235. This sub-study was not registered separately.